NYANYIAN BAGANDU MASYARAKAT SIAK HULU KABUPATEN KAMPAR DAN IMPLIKASINYA PADA MATA PELAJARAN IPS SD - Emilia Susanti (Lembaga penelitian dan pengabdian kepada Masyarakat, 2016)
The objective of this research was get an idea of a comprehensive and holistic understanding on the implementation and functions ofbaghandu song of the community of Siak Hulu Kampar regency in the implementation of IPS in elementary education. This research used Qualitative method. Data was collected by observation, interview and documentation. It used snowball sampling. The subjects were the elders of suku Pandan, the humanists who work at Melayu traditional organization at Siak hulu Kampar regency, Rebana groups and teachers who teach at elementary school of Desa Kubang Jaya of Siak hulu Kampar regency. The research finding showed that (1) implementation of community singing baghandu Siak Hulu Kampar regency was originally done by mothers who euthanize the children, singing bagandu also be held on the aqiqah (2) the function of Baghandu songs are: (a) for the moral formation (b) for educational transformation (c) for identity formation (d) as a bastion of the influx of foreign cultures (3) the application of Baghandu songs: (a) the means for national identity formation (b) increasing the quality of history and social sciences or learning resources, (c) as a means of preservation of local cultural heritage, especially the local Malay culture Kampar.